Misconceptions Analysis of Biology Textbooks for First Grade of Senior High School of the 2013 Curriculum on Protist Lesson - Elnissa, Aura; Jayanti, Ummi Nur Afinni Dwi (Universitas Labuhanbatu, 2023)
This research aims to determine the misconceptions and the category of misconception found, and the percentage of misconceptions found in biology textbooks on first grade of senior high school curriculum 2013 for Protist material. This type of research is content analysis. The research sample consisted of 3 biology textbooks on first grade of senior high school curriculum 2013, selected using a purposive sampling technique which had previously been observed in several schools in Medan. The object of this research is the material concepts of Protist. The analysis of misconceptions in this study was based on Hershey's five categories of misconceptions, Oversimplifications, Overgeneralizations, Obsolete concepts and terms, Misidentification, and Undergeneralization. The results showed that in Book A there were 2 misconceptions found,namely in the Oversimplications and Undergeneralization. In Book B there are 4 misconceptions, namely in the Oversimplication and Misidentifications. In Book C there are 3 misconceptions, namely in the Oversimplications.The percentage of misconception categories found were Oversimplifications (0.83%), Misidentifications (0.11%), and Undergeneralization (0.11%). Meanwhile, the Overgeneralizationsand Obsolete concepts and terms categories were not found in the three textbooks